Estudio de prefactibilidad de una planta productora de snacks a base de fruta deshidratada cubierta con chocolate [piña (ananas comosus), mango (Mangifera indica) y plátano (Musa paradisiaca)] - Franco Campos, Luis Ayrton (2022)
In recent years, people are more involved in having a healthy lifestyle and part of this is reflected in the diet. A trend has been seen in people's preferences for healthy eating. It is for this reason that the idea for this project arose. The main objective of the study is to determine the technological, market, economic, financial, social and enviornmental viability for the installation of a plant that produces dehydrated fruit snacks covered with chocolate. Fruits provide vitamins, minerals, and fiber needed to support a healthy digestive system, while dark chocolate, high in cocoa, contains antioxidants and can help burn fat. In the market study part, it was possible to attract a target audience belonging to the inhabitants of Metropolitan Lima, from socioeconomic levels A and B, over 18 years old and have some interest in having a healthy lifestyle. The demand for this project was estimated at 38 406 kg of product for the year 2026. It was determined that the best location for the snack production plant is the industrial zone of the city of Satipo and that there should be a warehouse for finished products in the city of Lima. In addition, the required space of this plant will be 663 square meters. Finally, in the economic and financial analysis, it was estimated that with the expected sales based on the market study and with an initial investment of S/ 799 304, it is expected to obtain an economic NPV of S/ 2 236 195 and an economic IRR of 84,69%. On the other hand, a financial NPV of S/ 2 268 820 and a financial IRR of 110,67%. Both indicators show that the project would be profitable economically and successful.